2022
DOI: 10.5933/jkapd.2022.49.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acid Resistance of Demineralized Dentin after Silver Diamine Fluoride and Potassium Iodide Treatment

Abstract: This study investigated the effects of silver diamine fluoride (SDF) and potassium iodide (KI) treatments on the acid resistance of dentin exposed to secondary caries. Sixteen bovine dentin specimens with artificially induced caries were assigned to the following four groups: untreated negative control, untreated positive control, SDF-treated (SDF), and SDF and KI-treated (SDFKI). Multispecies cariogenic biofilms containing <i>Streptococcus mutans</i>, <i>Lactobacillus casei</i>, and &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The ease of use is useful in treating large numbers of patients as a treatment modality for the prevention of caries ( 2 ). Various formulations of SDF have been assessed in the literature for caries remineralization, and the subsequent acid resistance of treated teeth ( 3 ) improved changes in the surface’s micro-hardness ( 4 , 5 ); the management of carious lesions as a result of molar incisor hypomineralization have been recorded ( 6 ). It has been realized that teeth usually treated with various SDF products have large active cavitated carious lesions, with the tooth very well at the end of its life span.…”
Section: Introductionmentioning
confidence: 99%
“…The ease of use is useful in treating large numbers of patients as a treatment modality for the prevention of caries ( 2 ). Various formulations of SDF have been assessed in the literature for caries remineralization, and the subsequent acid resistance of treated teeth ( 3 ) improved changes in the surface’s micro-hardness ( 4 , 5 ); the management of carious lesions as a result of molar incisor hypomineralization have been recorded ( 6 ). It has been realized that teeth usually treated with various SDF products have large active cavitated carious lesions, with the tooth very well at the end of its life span.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment strategies for this malignancy include chemotherapy, radiation therapy (RT), hematopoietic stem cell transplantation (HSCT), and immunotherapy [4]. Meanwhile, dental developmental disturbances caused by these treatments include microdontia, short roots, root shunting, delayed or arrested dental development, enamel hypoplasia, abnormal crown size, and multiple tooth agenesis [5][6][7]. A previous study reported that the incidence of hypodontia and microdontia was higher in cancer survivors who received anticancer treatment before the age of 4 years [8].…”
Section: Introductionmentioning
confidence: 99%